Power Distance Belief and Impulsive Buying - Zhang, Yinlong; Winterich, Karen Page; Mittal, Vikas (Journal of Marketing Research, 2010)
The authors propose that power distance belief (PDB) (i.e., accepting and expecting power disparity) influences impulsive buying beyond other related cultural dimensions, such as individualism–collectivism. This research supports an associative account that links PDB and impulsive buying as a manifestation of self-control, such that those with high PDB display less impulsive buying. Furthermore, this effect manifests for vice products but not for virtue products. The authors also find that restraint from temptations can occur automatically for people who have repeated practice (i.e., chronically high PDBs). Taken together, these results imply that products should be differentially positioned as vice or virtue products in accordance with consumers’ PDBs.